Transcriptomic responses of water buffalo liver to infection with the digenetic fluke Fasciola gigantica - Zhang, Fu-Kai; Zhang, Xiao-Xuan; Elsheikha, Hany M.; He, Jun-Jun; Sheng, Zhao-An; Zheng, Wen-Bin; Ma, Jian-Gang; Huang, Wei-Yi; Guo, Ai-Jiang; Zhu, Xing-Quan (BioMed Central, 2017)
Background Fasciola gigantica, the tropical liver fluke, infects buffaloes in Asian and African countries and causes significant economic losses and poses public health threat in these countries. However, little is known of the transcriptional response of buffaloes to infection with F. gigantica. The objective of the present study was to perform the first transcriptomic analysis of buffalo liver infected by F. gigantica. Understanding the mechanisms that underpin F. gigantica infection in buffaloes will contribute to our ability to control this parasite. Methods We challenged buffaloes with 500 viable F. gigantica metacercariae and collected liver samples through a time course at 3, 42 and 70 days post-infection (dpi). Then, we performed gene expression analysis on liver samples using RNA sequencing (RNA-Seq) Illumina technology and confirmed the RNA-Seq data by quantitative RT-PCR analysis. Results Totals of 496, 880 and 441 differentially expressed transcripts were identified in the infected livers at 3, 42 and 70 dpi, respectively. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that transcriptional changes in the liver of infected buffaloes evolve over the course of infection. The predominant response of buffaloes to infection was mediated by certain pathways, such as MHC antigen processing and presentation, Toll-like receptor 4 (TLR4), transforming growth factor beta (TGF-β), and the cytochrome P450. Hepatic drug metabolizing enzymes and bile secretion were also affected. Conclusions Fasciola gigantica can induce statistically significant and biologically plausible differences in the hepatic gene expression of infected buffaloes. These findings provide new insights into the response of buffaloes to F. gigantica over the course of infection, which may be useful in determining pathways that can modulate host-parasite interaction and thus potentially important for clearance of the parasite.